Security Design for Local Area Networks Using Port Firewall Security - Pukeng, Ahmad Fahrijal; Havid, Hervan (Sebatik, 2025)
Network security design is a crucial aspect in maintaining data integrity, confidentiality, and availability. This study develops and tests an effective network security system using the firewall security port method. This method focuses on identifying and restricting access to physical switch ports to prevent unauthorized access and protect the system from external threats. The research method uses experimental stages through subjective means to describe current practices. Through configuration and testing in a simulated environment, this study shows that the implementation of MAC address-based port security effectively blocks illegal devices without disrupting the connectivity of legitimate devices. This study provides evidence and practical guidelines that the firewall security port method is an efficient solution for improving network access layer security. The conclusions of this study provide a basis for organizations to implement proactive security measures in the face of evolving cyber threats.